Musical roads: design, construction and potential economic and safety benefits. Issue 6 (21st December 2020) - Zhou, Man; Huang, Dongqi; Hu, Yaqing; Zhou, Lingyu; An, Lin
Abstract : There are more than 30 stretches of road in the world (mostly in Japan) that use rumble strips to create musical notes as cars drive along them. This paper discusses the three main structural forms and construction methods used to create the musical effect. Beyond their economic value as a tourist attraction, some 'musical roads' have been used in dangerous stretches to discourage speeding, with the melody providing a warning or only being recognisable at a safe speed.